Indirect regulation of topsoil nutrient cycling by groundwater depth: impacts on sand-fixing vegetation and rhizosphere bacterial communities - Hao, Lianyi; Liu, Xiuhua; Ji, Ruiqing; Ma, Yandong; Wu, Puxia; Cao, Qingxi; Xin, Yunling (Frontiers in Microbiology, 2023)
Introduction The impact of groundwater table depth (GTD) on bacterial communities and soil nutrition in revegetated areas remains unclear. Methods We investigated the impacts of plant growth and soil physicochemical factors on rhizosphere bacterial communities under different GTD. Results The four plant growth indices (Pielou, Margalef, Simpson, and Shannon-Wiener indices) and soil water content (SWC) at the Artem and Salix sites all showed a decreasing trend with increasing GTD. Salix had a higher nutrient content than Artem. The response of plant rhizosphere bacterial communities to GTD changes were as follows. Rhizosphere bacteria at the Artem and Salix sites exhibited higher relative abundance and alpha diversity in SW (GTD < 5 m) compared than in DW (GTD > 5 m). Functional microbial predictions indicated that the rhizosphere bacterial communities of Artem and Salix promoted carbon metabolism in the SW. In contrast, Artem facilitated nitrogen cycling, whereas Salix enhanced both nitrogen cycling and phototrophic metabolism in the DW. Discussion Mantel test analysis revealed that in the SW of Artem sites, SWC primarily governed the diversity of rhizosphere and functional bacteria involved in the nitrogen cycle by affecting plant growth. In DW, functional bacteria increase soil organic carbon (SOC) to meet nutrient demands. However, higher carbon and nitrogen availability in the rhizosphere soil was observed in the SW of the Salix sites, whereas in DW, carbon nutrient availability correlated with keystone bacteria, and changes in nitrogen content could be attributed to nitrogen mineralization. This indicates that fluctuations in the groundwater table play a role in regulating microbes and the distribution of soil carbon and nitrogen nutrients in arid environments.